Investigation of a cost‐effective finite difference scheme for the transport equation - Slugin, D. G.; Popov, A. V. (Mathematical Modelling and Analysis, 2003)
The transport equation for three‐dimensional flow of a viscous gas is considered. An implicit finite difference scheme is constructed for approximating the transport equation. The error estimation is proved. The main part of the analysis is done for the first differential approximation of the proposed finite difference scheme, but the results are also valid in the fully discrete case. Ekonomiškų baigtinių skirtumų schemų pernešimo lygčiai tyrimas Santrauka. Straipsnyje nagrinėjama trimačių klampių dujų tekėjimo pernešimo lygtis. Pateikta neišreikštinė baigtinių skirtumų schema aproksimuojanti šią pernešimo lygtį. Įrodytas paklaidos įvertis. Pagrindinė tyrimo analizė atlikta pateiktos baigtinių skirtumų schemos pirmos eiles diferencialiniam artiniui. Analogiški rezultatai pasilieka teisingi ir pilnai diskrečiuoju atveju. First Published Online: 14 Oct 2010